Two-dimensional oxygen clusters and films adsorbed on graphite - Pan, Ru-Pin Chao, author; Etters, Richard D., advisor; Sites, James R., committee member; Johnson, Gearold R., committee member; Gillis, Nelson S., committee member (Colorado State University. Libraries, 1981)
The orientations, structures and phase transitions of two-dimensional oxygen molecular clusters adsorbed on the graphite plane were studied using the Monte-Carlo method. Orientational phase transitions have been found for all cluster sizes studied. Melting temperatures show agreement with measured values for extremely low coverage films. Two different approximations were used in the cluster studies. In one approximation, the interaction between a cluster and the surface was ignored and the center of mass of each oxygen molecule was fixed on a plane. In the other case an atom-atom Lennard-Jones potential was used to determine the surface interaction. An analytic expression was used for the summation over all the carbon atoms in the graphite. The minimal energies and structures of infinite adsorbed films were studied using an energy minimization method. Two stable phases have been found. The molecules in the low density phase are all oriented parallel to the substrate, while the molecules in the high density phase are perpendicular to the substrate. These two phases are identified as the experimentally measured δ and β phases, respectively. The lattice constants are found to be in agreement with the measured values within 3%.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Molecular dynamics; Monte Carlo method